PENGARUH DISPOSISI BERPIKIR KRITIS TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN PEMECAHAN MASALAH SISWA - Maya Alia Puspita; Friyatmi (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to analyze the influence of critical thinking disposition on critical thinking skills and problem-solving skills. The background of this study is the low level of students' problem-solving skills caused by several factors including Critical Thinking Skill (CTS) and Critical Thinking Disposition (CTD). This study uses a quantitative approach with an associative method. The sample consisted of 100 students of grade XI of SMAN 2 Sungai Penuh using a sampling technique, namely proportional random sampling. Data collection was carried out through 2 types of instruments, namely written tests in the form of questions (objective, essay) and a Likert scale, then analyzed using SPSS version 27. The results of the study indicate that critical thinking disposition has a direct effect on problem-solving skills. This influence is not mediated by students' critical thinking skills. These findings indicate that students' internal attitudes and tendencies in critical thinking can influence students' ability to solve problems independently.